Capital Account Opening and Wage Inequality - Larrain, Mauricio (Review of Financial Studies, 2015)
Opening the capital account allows financially constrained firms to raise capital from abroad. Since capital and skilled labor are relative complements, this increases the relative demand for skilled labor versus unskilled labor, leading to higher wage inequality. Using aggregate data and exploiting variation in the timing of capital account openings across 20 mainly European countries, I find that opening the capital account increases aggregate wage inequality. In order to identify the mechanism, I use sectoral data and exploit variation in external financial dependence and capital-skill complementarity across industries. I find that capital account opening increases sectoral wage inequality, particularly in industries with both high financial needs and strong complementarity.